2018
DOI: 10.33089/jthort.v1i1.7
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Transpiration and Calcium Fertilization on Mangosteen (Garcinia mangostana L.) Seedlings

Abstract: The availability of nutrients in plants depends on the ability of plants to absorb nutrients from the soil. One of the processes absorbed by plants is by the presence of the transpiration process.  Good transpiration will provide enough nutrients for plants which increase the productivity and quality of mangosteen. One of the quality standards of mangosteen fruit for export quality is the free from yellow sap contamination. It can be possible that transpiration can improve the quality of mangosteen fruit by ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…e transpiration rate is closely related to leaf area. As shown by Akmal et al (2018), plants with larger leaves have a higher transpiration rate, in turn, according to Dulbari et al (2018), the relationship between stomatal conductance and the ability of photosynthesis and transpiration is important aspect in relation to environment responses. us, lime plants still need to be studied further with consideration of some influencing factors, such as the greenness of leaves/chlorophyll content, water availability, and solar energy factors to better understanding on self-pruning incidents.…”
Section: Discussionmentioning
confidence: 99%
“…e transpiration rate is closely related to leaf area. As shown by Akmal et al (2018), plants with larger leaves have a higher transpiration rate, in turn, according to Dulbari et al (2018), the relationship between stomatal conductance and the ability of photosynthesis and transpiration is important aspect in relation to environment responses. us, lime plants still need to be studied further with consideration of some influencing factors, such as the greenness of leaves/chlorophyll content, water availability, and solar energy factors to better understanding on self-pruning incidents.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Akmal et al. (2023) reported that mangosteen fruit, located either outside or inside the canopy, that were enclosed with either transparent or black plastic bags showed no differences in fruit color development. The α‐mangostin content in the pericarp increased markedly during the 10‐ to 14‐week period after anthesis, and that increase was not affected by bagging, bagging materials, or application periods (Widodo et al., 2021).…”
Section: The Impacts Of Light On Anthocyanin Contentmentioning
confidence: 92%